Analisis Perbandingan Purchase Intention Pada Aplikasi Online Food Delivery (OFD) Di Indonesia: Indonesia - Samiono, Bambang Eko; Pratiwi, Ramadhanty (Asian Journal of Innovation and Entrepreneurship, 2024)
In Indonesia, online food delivery (OFD) services consist of 2 (two) types, namely OFD by Platform and OFD by restaurant apps.  Data shows that users of OFD by restaurant apps are ahead year-on-year compared to OFD by Platform users. This proves that although these 2 (two) types of applications are in the same industry and provide the same service, namely online food delivery (OFD), they still have differences that are influenced by certain factors. The study aims to analyze differences in Purchase Intention on Platform-Based Online food delivery Applications (Go food, Grab food and Shopee food) and Restaurant (KFCKU, Pizza Hut Indonesia and McDelivery) by involving Online Customer Review variables, sales promotion, and Website Quality as well as the intervening variable e-trust. This research was conducted with 100 respondents. The sample collection technique in this study used purposive sampling technique. This study uses quantitative methods and path analysis tests. The results in this study explain that there is a direct influence between Online Customer Review (X1) and Website Quality (X3) on E-Trust (Z) in the OFD by Platform application and the OFD by restaurant application. In OFD by Platform, there is no direct influence between Sales Promotion (X2) and Website Quality (X3) on Purchase Intention (Y). In OFD by restaurant, there is no direct influence between Online Customer Review (X1) and Sales Promotion (X2) on Purchase Intention (Y). In addition, there is an indirect influence between Online Customer Review (X1) and Website Quality (X3) on Purchase Intention (Y) through E-Trust (Z).